Utilization of the Educational Environment as Media Learning in the 2013 Curriculum Implementation - Lestari, Sri (Tekno - Pedagogi : Jurnal Teknologi Pendidikan, 2021)
This research aims to explore the use of the school environment as a learning medium in the context of implementing the 2013 Curriculum in class IV at SDN 55/1 Sridadi. Using a descriptive qualitative approach, data was collected through observation, interviews and documentation. The research results show that teachers have actively used the school environment and used items as effective learning resources, by applying a scientific approach to increase student interaction and involvement in learning. The uniqueness of this approach is that it integrates the concept of a scientific approach from the 2013 Curriculum with the use of the school environment as a learning medium, which provides a more comprehensive and involved learning experience for students. The implications of this research are increasing the effectiveness and efficiency of learning as well as developing a learning environment that is more conducive to students' holistic development. In addition, these findings also open up space for further research in developing learning strategies that are relevant to the context of the school environment, which can enrich students' learning experiences and improve the overall quality of education.